ANALISIS KEMAMPUAN BERPIKIR KREATIF DAN PEMECAHAN MASALAH MATEMATIK SERTA KEPERCAYAAN DIRI SISWA SMP MENGGUNAKAN PENDEKATAN KONTEKSTUAL - Anisa Rosyanti; Agus Roheandi; Luvy Sylviana Zanthy (Journal on Education, 2019)
This study aims to find out about creative thinking skills and mathematical problem solving and the confidence of junior high school students using a contextual approach. This research is descriptive study qualitative questions research. This research was held in one of the junior high schools in the west Bandung regency, the subject of this study was the class VIII B students of the Satap Lembang junior high school in Cililin. Data analysis is done by data reduction techniques, data presentation and conclusion drawing mathematical creative thinking ability is an ability in wich student are able to provide various answers to the given, they are able to see a problem not only based on one point of view but more than that, they are able to record a problem in detail so that is more interesting to study, able to express answers in different ways than they have ever been, and be able to explore them into various answers. Mathematical problem solving is the ability of students to find solutions or ideas regarding the goals to be achieved, througha activities to understand problems, plan activities, or design problem solving strategies, carry out calculations, and examine the result or solutions. While self-confidence is a belief of someone who is able and able to deal with situations that exist and are being faced, both the circumstances in themselves and their environment. People who have their self-confidence will be able to judge themselves whether it is positive or negative, can position themselves properly, not depend on others to make a decision. He is able to face all the risks that exist and can recognize himself well. By using a contextual approach which ai an approach that connects exisiting learning with real life or maybe experienced by students, it is expected that students will easily apply it in learning activities.